Assessing the pros and cons of vaginal birth after caesarean relative to elective repeat caesarean section - Prasad, Sangeeta G.; Malhotra, Preeti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Recent years have witnessed a rise in rate of primary caesarean section (CS). No. of women reporting with a previous CS scar is also increasing. Judicious trial of labor in such patients can prevent repeat caesarean section. Aim of this study was to assessing the safety and success rate of vaginal birth after caesarean (VBAC) in selected cases of patients who have undergone previous lower segment CS (LSCS) is the main aim of this study. Methods: In this prospective observational study carried out in a tertiary care teaching hospital over a period of 1 year. 375 pregnant women with a history of one previous LSCS for non-recurrent indications were enrolled. The statistical technique of t-test was administered for relative comparison with respect to maternal and neonatal complications across the two groups, i.e. repeat LSCS and vaginal delivery. Results: Out of 375 patients 187 patients (49.9%) underwent elective LSCS for recurrent indication and for non-recurrent indication associated with some complicating factor. Trial of labor in 188 (50.10%) was given out of which 59.3% had spontaneous vaginal delivery,7.20% had instrumental delivery and 33.50% landed into emergency CS. Commonest cause of Em. LSCS being Fetal distress. As regards maternal complications, no statistically significant difference was found between the Repeat LSCS and Vaginal delivery groups (t = 0.779, p > 0.05). On similar lines, there was no statistically significant difference across both groups as regards neonatal complications (t = 0.632, p > 0.05). Conclusions: Taking into account the increased trend of primary CS, trial of VBAC in selected cases is very important. It can be concluded that VBAC has chances of success in cases with previous one LSCS but it must be carefully investigated and monitored.